P305 Intra-cavitary contrast-enhanced ultrasound: A novel radiation-free method to detect abscess associated internal fistulas in Crohn's disease. (16th January 2018) - Mao, R; Chen, Y -j; Rimola, J; Rieder, F; Ben-Horin, S; Chen, M -h; Xie, X -y
Abstract: Background: Internal penetrating disease is a common condition complicating Crohn's disease (CD). Establishing the presence of a fistula and the anatomical definition of the fistulous tracts are essential for deciding on appropriate treatment strategies. We aimed to assess the diagnostic accuracy of intra-cavitary contrast-enhanced ultrasound (IC-CEUS) for the detection of internal penetrating disease associated with abscesses in CD patients and compared it to CT/MR enterography (CTE/MRE), using surgical findings as the reference standard. Methods: In this prospective cohort study, consecutive CD patients with suspicion for an intra-abdominal abscess, who were referred for US-guided aspiration followed by surgical intervention were recruited. IC-CEUS was performed by injecting diluted contrast agent (Sonovue) into the abscess cavity immediately following the ultrasound-guided needle abscess aspiration and drainage. Diagnostic accuracy of IC-CEUS in demonstrating the correct anatomy of fistulous tracts was compared with CTE/MRE in the same patient vis-à-vis surgery findings as the gold standard. Results: In the 34 patients undergoing IC-CEUS, 31 patients who underwent subsequent surgery were included in the final analysis: 15 cases with fistulous tracts on CTE/MRE and 16 without fistulous tracks on CTE/MRE. All 31 patients were found to have fistulous tracts on surgical exploration. Overall, IC-CEUS demonstrated fistulous tracts in 26 of 31 participants with sensitivity and specificity of 86.7% and 100%, respectively, compared with surgical evaluation as the gold standard. Moreover, IC-CEUS correctly demonstrated fistulous tracks in 13 participants with negative findings on CTE/MRE. Combining IC-CEUS and CTE/MRE, the fistula tract was clearly demonstrated in 29 patients (93.5%, 29/31). The mean duration of the IC-CEUS procedure was 8.6 min (range 5.0–12.0 min). No severe adverse events occurred during IC-CEUS procedure. Conclusions: In this pilot study, IC-CEUS accurately detected internal fistulous tracks associated with intra-abdominal abscesses in CD patients with definite fistula confirmed at surgery. IC-CEUS correctly delineated fistula anatomy. As a radiation-free and safe technique, IC-CEUS may be used as an alternative/adjunctive method to CTE/MRE for detecting internal penetrating disease in patients with CD.